Effect of Content Marketing, Price Discount, and Social Influence On Purchase Decision Through Purchase Intention: A Study on the Instagram Followers of Beauty Store Mitufaya in Malang - Shiddiqy, Isymayati Ash; Pratikto, Heri (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the influence of content marketing, price discounts, and social influence on purchase decisions, mediated by purchase intention. The research targets Instagram followers of the Mitufaya beauty store in Malang, Indonesia, using a descriptive and explanatory quantitative approach. A total of 186 followers were selected as the sample. Data were analyzed using Structural Equation Modeling (SEM) via SmartPLS. Results show that content marketing and price discounts significantly affect both purchase intention and decision. Social influence significantly affects purchase intention but not purchase decision. Purchase intention significantly mediates the effects of all independent variables on purchase decisions.